S100B Mediates Stemness of Ovarian Cancer Stem-Like Cells Through Inhibiting p53. (21st August 2016) - Yang, Tao; Cheng, Jianan; Yang, Yang; Qi, Wei; Zhao, Yuetao; Long, Haixia; Xie, Rongkai; Zhu, Bo
Abstract : S100B is one of the members of the S100 protein family and is involved in the progression of a variety of cancers. Ovarian cancer is driven by cancer stem-like cells (CSLCs) that are involved in tumorigenesis, metastasis, chemo-resistance and relapse. We then hypothesized that S100B might exert pro-tumor effects by regulating ovarian CSLCs stemness, a key characteristic of CSLCs. First, we observed the high expression of S100B in ovarian cancer specimens when compared to that in normal ovary. The S100B upregulation associated with more advanced tumor stages, poorer differentiation and poorer survival. In addition, elevated S100B expression correlated with increased expression of stem cell markers including CD133, Nanog and Oct4. Then, we found that S100B was preferentially expressed in CD133 + ovarian CSLCs derived from both ovarian cancer cell lines and primary tumors of patients. More importantly, we revealed that S100B knockdown suppressed the in vitro self-renewal and in vivo tumorigenicity of ovarian CSLCs and decreased their expression of stem cell markers. S100B ectopic expression endowed non-CSLCs with stemness, which has been demonstrated with both in vitro and in vivo experiments. Mechanically, we demonstrated that the underlying mechanism of S100B-mediated effects on CSLCs stemness was not dependent on its binding with a receptor for advanced glycation end products (RAGE), but might be through intracellular regulation, through the inhibition of p53 expression and phosphorylation. In conclusion, our results elucidate the importance of S100B in maintenance of ovarian CSLCs stemness, which might provide a promising therapeutic target for ovarian cancer.